PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA PUSAT KESEHATAN MASYARAKAT DI DESA KALEKE KECAMATAN DOLO BARAT KABUPATEN SIGI - Lestari, Wanda Try; Suasa; Erdiyansyah (JPS: Journal of Publicness Studies, 2025)
This study aims to determine whether there is an influence of service quality on patient satisfaction at Kaleke Health Center located in Kaleke Village, West Dolo District. The data collected includes primary and secondary data. Data collection methods involve library research, observation, questionnaires, and documentation. To complete the data in this study, the researcher distributed questionnaires to 100 respondents with a total population of 2508 individuals. This research uses the Service Quality Theory by Parasuraman, Zeithhaml, and Berry (2011), and Patient Satisfaction from Boy S. Sabarguna (2008). The data analysis technique used is simple linear regression. Based on the research results, it is shown that the service quality variable has a positive effect on patient satisfaction at Kaleke Health Center in Kaleke Village, West Dolo District, as indicated by the F value being greater than the F table, with an F value of 116.817 and an R value of 0.737, which is in the interval indicating a "strong" influence. This means that if the quality of service changes, patient satisfaction will also experience a strong change.